Andrographolide Pretreatment Enhances the Bioavailability and Hypoglycemic Action of Glimepiride and Metformin - Sujatha Samala; Ciddi Veeresham (International Journal of Phytomedicine, 2015)
Herbal antidiabetic preparations are often used as an add-on therapy in diabetes. Hence, in the present investigation the effect of andrographolide (AD) on the pharmacokinetics and pharmacodynamics of glimepiride and metformin in normal as well as in STZ - induced diabetic rats was studied. In normal and diabetic rats the combination of glimepiride and metformin with AD increased significantly (p < 0.01) all the pharmacokinetic parameters, such as Cmax, AUC0 to n, AUCtotal, t½, MRT and decreased the clearance, Vd markedly as compared with the control group. In pharmacodynamic studies, the combination of glimepiride and metformin with AD provided significant protection against the diabetes induced alterations in the biochemical parameters. In addition, the combination of glimepiride and metformin with AD also improved the total antioxidant status and decreased lipid peroxide levels significantly in diabetic rats compared with AD, glimepiride and metformin alone treated groups. The results revealed that combination of glimepiride and metformin with AD led to the enhancement of the bioavailability of glimepiride and metformin by inhibiting the CYP450 enzymes. In conclusion, add-on preparations containing AD may increase the bioavailability of glimepiride and metformin, which suggested that AD might be beneficial as an adjuvant to glimepiride and metformin in a proper dose, in diabetic patients and hence the doses should be monitored.